2020
DOI: 10.1111/dth.14386
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional immunotherapy for molluscum contagiosum: A review

Abstract: Molluscum contagiosum (MC) is a common cutaneous viral infection with no standard treatment. The virus responsible for MC is thought to be cleared by cell mediated immunity (CMI). Intralesional immunotherapy that stimulates CMI has been shown to be an effective treatment for other cutaneous viruses. In this review, we evaluate the efficacy and safety of intralesional immunotherapy in the treatment of MC. Articles met inclusion criteria if they examined the effects of intralesional immunotherapy as a treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…However, many patients--and especially older sexually active individuals--prefer interventional therapy. These modalities include mechanical methods, chemical methods, immunomodulatory methods, and antiviral therapy [ 1 , 2 , 4 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many patients--and especially older sexually active individuals--prefer interventional therapy. These modalities include mechanical methods, chemical methods, immunomodulatory methods, and antiviral therapy [ 1 , 2 , 4 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…[41] e topical immunomodulatory methods that have been tried in molluscum contagiosum are 5% imiquimod cream, diphencyprone, and topical sinecatechins. [2][3][4][5][6][7] Al-Mutairi et al, in a prospective, randomized, comparative, and observerblinded study, found imiquimod 5% cream applied 5 days a week to be of comparable efficacy (complete cure rate 91.8%) to weekly cryotherapy (complete cure rate 100%) at the end of 16 weeks. Pain, bullae formation, pigmentary changes, and superficial scarring were significantly more in the cryotherapy group.…”
Section: Molluscum Contagiosummentioning
confidence: 99%
“…[2] Intralesional immunotherapies [Table 2] used in molluscum contagiosum include measles-mumps-rubella vaccine, Candida, tuberculin PPD, vitamin D3, interferon α, and Streptococcal substrain OK-432. [5][6][7] Nelson et al reported 10 patients with HIV infection who received intralesional IFN α (one mega unit) at weekly intervals for 4 weeks. ree Mollusca of each patient were chosen for treatment.…”
Section: Cutaneous Wartsmentioning
confidence: 99%
See 2 more Smart Citations